PENGARUH PEMIKIRAN ORIENTALIS TERHADAP PEMIKIR MUSLIM MODERN (Studi Tentang Sunnah Sebagai Sumber Tasri') - Kholidah Kholidah (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2016)
The orientalists studies about authenticity and originality of the prophet Muhammad Sunnah as a source of tasri’ have influenced a number of modernist muslim thinker, among these are Ahmad Amin, Muhammad Syahrur and Mahmud Abu Rayyah. Over their thoughts about the sunnah, less precise, considering they actually still acknowledge hadith or sunnah as sources of tasyri’. What happens is they criticize the method used by classical sholar in detecting false hadith, then offer methods that they assume more precise. Because the classical scholar still propose that hadith is shahih but actually not for them.